Al-Ḍaḥḥāk bayna al-Sard al-Fārisī wa al-‘Arabī fī al-Turāth al-Islāmī: Taḥlīl Tārīkhī wa Muqāranah Fikrīyah - Yousif, Tawfeeq Rashid (Indonesian Journal of Islamic Literature and Muslim Society, 2025)
The legend of al-Dahhāk represents one of the most complex mythological narratives transmitted through both Persian and Arabic Islamic historiography. Rooted in pre-Islamic mythic traditions, this figure has been reinterpreted by Muslim historians to reflect evolving cultural, political, and theological contexts. This study aims to analyze the historical and intellectual dimensions of the al-Dahhāk narrative through a comparative examination of Persian and Arabic Islamic sources. Employing a historical-analytical comparative method, the research draws upon early primary sources such as al-Ṭabarī, al-Masʿūdī, al-Bīrūnī, and Firdawsī’s Shāhnāmah, alongside the Avesta as a pre-Islamic reference text. The analysis reveals significant divergences between Arabic and Persian accounts regarding al-Dahhāk’s origin, identity, and geography. While Arabic sources often associate him with Yemen or Babylon, Persian traditions depict him as a tyrant linked to the ancient Iranian dynasties. The study argues that al-Dahhāk symbolizes not a single historical individual but a dynastic archetype—possibly representing the Assyrian Empire—whose reign embodies tyranny and decline. By reinterpreting myth through historical critique, this research contributes to a deeper understanding of how Islamic historiography assimilated mythic structures from Persian and Mesopotamian traditions, illuminating the interplay between history, legend, and identity in the early Islamic intellectual heritage.